Effect of sea water on composite material's properties - Cai, Huiying (2013)
Composites are an emerging field of material that is under intensive research by many researchers, as it possesses exceptional mechanical properties with the most outstanding being their high strength-to-weight ratio. They also offer good corrosion resistance and thus are highly suitable for marine applications.